PELAKSANAAN SUPERVISI PENDIDIKAN PADA MADRASAH ALIYAH NEGERI 1 SIGLI - Yusmadi .; Jamaluddin Idris; Nasir Usman (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2012)
Abstract: Educational supervision is an effort of teachers’ establishment for improving the quality of teaching learning process in school or madrasah. The purposes of this research were aimed to find out: 1) the program of educational supervision. 2) the technical of educational supervision. 3) the process of educational supervision and 4) to follow-up the educational supervision. The approach used in this research is a qualitative approach with descriptive method. To gain the data needed, the writer applied some techniques; observation, interview and documentation. The subjects of this research were the supervisors from The Ministry of Religious Affairs Pidie, the principal, the vise principal and the teachers MAN 1 Sigli. After analyzing the data, it has been found that: 1) the program of educational supervision organized at the beginning of the semester each year by the supervisors, the principaland the senior teacher. Supervision program includes the analysis of teachers’ ability, development of teaching learning process, development of teacher professionalism and development of curriculum analysis. 2) the appli-cation of educational supervision technique has not been optimized, so, it could not reveal the weakness of teaching learning process in detail. 3) the imple-mentation of educational supervision was conducted in regular schedule byeach teacher, the process would done through a meeting before observation, obser-vation of teaching learning process and a meeting after observation. 4) the findings of educational supervision followed by the supervisor through humanistic and professional approach. Keywords : Educational Supervision and Teaching Learning Process